Past, present, and future of Parkinson's disease: A special essay on the 200th Anniversary of the Shaking Palsy. Issue 9 (9th September 2017) - Obeso, J.A.; Stamelou, M.; Goetz, C.G.; Poewe, W.; Lang, A.E.; Weintraub, D.; Burn, D.; Halliday, G.M.; Bezard, E.; Przedborski, S.; Lehericy, S.; Brooks, D.J.; et al.
ABSTRACT: This article reviews and summarizes 200 years of Parkinson's disease. It comprises a relevant history of Dr. James Parkinson's himself and what he described accurately and what he missed from today's perspective. Parkinson's disease today is understood as a multietiological condition with uncertain etiopathogenesis. Many advances have occurred regarding pathophysiology and symptomatic treatments, but critically important issues are still pending resolution. Among the latter, the need to modify disease progression is undoubtedly a priority. In sum, this multiple‐author article, prepared to commemorate the bicentenary of the shaking palsy, provides a historical state‐of‐the‐art account of what has been achieved, the current situation, and how to progress toward resolving Parkinson's disease. © 2017 International Parkinson and Movement Disorder Society